Some studies on allelopathy of Rumex crispus L. and Polygonum segetum HBK., in Colombia (2003)
Curly dock (Rumex crispus, ‘lengua de vaca’) and smartweed (Polygonum segetum, ‘gualola’), are two common weed species that grow in subtropical areas of the world, where cause great losses in crops and grasslands due to their aggressiveness. In Colombia they are found on lands over 2000 m.o.s.l., and as they propagate by both, sexual and vegetative ways, it is very difficult to manage them. Several experiments were carried out in order to standardize the extraction methods, identify the extracts due to secondary metabolism from plants of Rumex and Polygonum, and evaluate the effects of such compounds over the germination and development of various species of plants. It was possible, through bioassays, to establish that watery extracts from the leaves and the roots contain allelopathic substances that increase the competitive ability of these weed species. On the other hand, qualitative analyses allowed identifying several allelopathic compounds like flavonoids. Initial bioassays were conducted over three groups of plants of R. crispus through experiments with ethanolic extracts and colored tests that confirmed the presence of flavonoids, terpenes, sesquiterpenlactones, quinones, alcaloids, glycosides and cumarines in plants of smartweed in those three growth states. Chalcones, aurones and flavonoles were detected as well as antraquinone and terpene glucosides, but not so, alcaloides.These results could become useful for advancing studies since they amplify the knowledge about allelopathic substances of these weed species, and show their potential use in managing plant-weed relation programs.